INFLUENCE OF BINDERS, MIX PROPORTIONS, AND FABRICATION METHOD ON THE CHARACTERISTICS OF FLY ASH AGGREGATE (Advances in Civil and Architectural Engineering, 2023)
In this paper, two types of lightweight fly ash (FA) aggregates: cold bonded fly ash (CFA) and sintered fly ash (SFA) aggregates were prepared through the cold bonding and sintering method. During the pelletization process, different ratios of binders to fly ash were used, i.e., 10:90, 15:85, 17:83, and 20:80 with a set amount of water. Cement, metakaolin, sodium silicate, urea-formaldehyde resin, bentonite powder, and phenol-formaldehyde resin were employed as binders. A comparative study on physicochemical, mechanical, phase identification, microstructure, and optical analysis of CFA and SFA was performed. The results showed that CFA (an alkali binder) had a higher water absorption (WA) value of 9,50 % with a crushing strength (CS) value of 6,30 MPa than SFA (sodium silicate binder) with a CS value of 5,80 MPa and a WA value of 10,28 %. Experimental observations also demonstrated that the leaching ability of SFA was considerably lower than that of CFA. Most notably, SFA can be used as a substitute for construction material and structural applications along with solving FA waste disposal and related problems to a considerable extent.